Deformation of the wave field interacting with offshore platforms: comparison between the corresponding results from a numerical model and a wave tank - Zaman, M. Hasanat; Akinturk, Ayhan (Volume 3: Structures, Safety and Reliability, 2016)
In the present research, a 3D dispersive numerical model has been developed and utilized to study the modification of the wave field in the presence of offshore structure. The Alternating Direction Implicit (ADI) algorithm has been employed for the solution of the governing equations. Relevant experiments are carried out in the Offshore Engineering Basin (OEB) of National Research Council (NRC) Canada. OEB is a 3D heavy duty 75m × 32m × 2.8m test facility equipped with modern data acquisition and tracking devices to record experimental data. Total 10 wave probes are deployed to measure the data at different locations in the Basin. Later the numerical results are compared with the experimental results. The comparisons of the numerical results show great agreement with the experimental results. Peer reviewed: Yes NRC publication: Yes